Baznas Micro-Crowdfunding: Risk Management-Based Organizational Design on the Transformation of Baznas Micro Zakat Bank - Pratama, Anggi Renaldy; Rofi, M Akhsanur (Journal of Management and Business Review, 2024)
Bank Zakat Micro (BZM) is a microfinance service initiated by BAZNAS to leverage ZIS-DSKL funds for providing capital to micro business mustahik under the al-Qardh principle, which entails interest-free financing. The main goal of this study is to develop a strategic model that transforms BCM’s operational framework into an independent institution capable of generating organizational revenue while fostering community participation in poverty alleviation. This applied research employs a qualitative descriptive approach to explain, design, and process data into a practically implementable model. The data collection technique was systematically performed using a sequential transformative strategy that involved stakeholder interviews, regional observations of BZM activities, and the analysis of internal and external institutional reports. using the method of interviews with stakeholders, observations of BZM in several regions, and document studies in the form of internal and external reports of the institution. The findings led to the creation of a risk-based organizational design to transform BZM into BAZNAS Micro-Crowdfunding, which is a crowdfunding service for Mustahik MSMEs in the form of KSPPS. Additionally, future BZM services are anticipated to encompass a combination of Qardh-based savings and loans, micro-crowdfunding investments, and assistance for Mustahik MSMEs. The research also outlines a comprehensive guide to implementing micro-crowdfunding schemes, from business processes to the impact assessment of the results, and demonstrates the practical applications of the study.